Perancangan Sistem Pencarian Ruangan Kosong Berbasis Website di Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh - Bustami (Journal Of Information Technology (JINTECH), 2023)
This research was motivated by several lecturers and students who were still having difficulty in finding empty classrooms at the State Islamic University of Ar-Raniry (UIN Ar-Raniry) Banda Aceh campus, especially at Tarbiyah and Teacher Training Faculty (FTK). This difficulty occurs because the system currently in use is still using manual methods. Therefore, this research was conducted to build a web-based system for finding empty class rooms that can be easily used by lecturers or students at FTK. The Prototype method was used to develop the system. The function of system that have been built were tested by using Black-box testing. The testing result shows that 93% of system functions work in accordance with their uses. This system is expected to be able to make a better contribution going forward in finding empty classrooms at FKT, UIN Ar-Raniry Banda Aceh